Arthroscopy Confers Excellent Clinical Outcomes in Femoroacetabular Impingement Syndrome (FAIS) Patients Aged 50 Years and Above. Issue 4 (16th January 2023) - Yang, Fan; Shi, Yuanyuan; Zhang, Zhu; Zhang, Xin; Huang, Hongjie; Ju, Xiaodong; Wang, Jianquan
Abstract : Objective: Hip preservation surgery has expanded to include treatment of hip pathology in elderly patients. Most data on efficacy of arthroscopy treatment in patients with femoroacetabular impingement syndrome (FAIS) has been generated from Western populations, while studies in the older Asian FAIS population are lacking. Here, we report efficacy of hip arthroscopy for treatment of Asian patients aged 50 years and above. Methods: We retrospectively reviewed data from 775 hips that were treated arthroscopically for FAIS between 2016 and 2019. Patients with a history of hip surgery, contralateral surgery during the follow‐up period, lateral center‐edge angle (LCEA) <25°, Tӧnnis grade ≥2, and incomplete records were excluded. Patient‐reported outcomes (PROs), such as modified Harris Hip Score (mHHS), Hip Outcome Score‐Activities of Daily Living (HOS‐ADL), International Hip Outcome Tool 12‐component form (iHOT‐12), and Visual Analog Scale (VAS) were compared pre‐ and post‐operation. We also recorded radiographic measures, intraoperative findings, procedures, complications, and subsequent surgical revisions. Finally, we correlated demographics with PRO improvement among the study group. Results: A total of 57 hips met the inclusion and exclusion requirements and were therefore included in the final analysis. After the follow‐up period (3.3 years), most patients exhibited significantly higher PROs than preoperative values, HOS‐ADL (65.0–81.7), iHOT‐12 (44.3–69.1), mHHS (58.9–81.7), and VAS (5.8–2.2; all p  < 0.001). Shorter symptom duration was significantly correlated with improved HOS‐ADL ( p  = 0.015), and mHHS score ( p  = 0.022). The overall rate of complications and rate of revisions were 5.3% and 7.0%, respectively, and none of the patients required total hip arthroplasty (THA). Conclusions: Arthroscopic surgery confers significant clinical outcomes in most FAIS patients in the Asian population who are aged 50 years and above. These benefits are accompanied by either a low revision rate or conversion to THA, while shorter symptom duration is positively correlated with improved HOS‐ADL and mHHS scores. Abstract : This study aimed to report at least 2‐year PROs of hip arthroscopic treatment among Asian patients aged 50 years and older and to analyze the relationships between demographics and PROs' score improvements.